Analisis Pengaruh Return On Equity (Roe), Earning Per Share (Eps) Dan Debt To Equity Ratio (Der) Terhadap Harga SahamPada Perusahaan Manufaktur Food and Beverage Yang Terdaftardi Bursa Efek Indonesia (BEI) Periode Tahun 2008-2014 - Puspitasari, Wulan; , Muzakar Isa, S.E, M.Si (2017)
The purpose of this study to measure the effect of Return On Equity (ROE), Earning Per Share (EPS), Deb to Equity Ratio (DER) to the stock price on Food and Beverage manufacturing companies listed on the Stock Exchange from 2008 to 2014 period. The data used is secondary data in the form of financial statements of companies acquired from the Indonesian Capital Market Directory (ICMD) and also www.idx.co.id.in the determination of this sample using purposive sampling method yatu determine the sample based on certain criteria. Anaisis method of data used is multiple linear regression analysis and hypothesis testing using t-statistic, the F-statistic, and the coefficient determinant. From the analysis during the study period t test is to determine the effect of individual independent variable on the dependent variable showed variable Return On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER) as a result of less than 0.05 means Ho rejected. While the F-test is used to determine the effect Return On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER) simultaneously to the stock price shows that F count equal to 16.472 with the sig. 0,000 less than 0.05 means Ho rejected and independent variables simultaneously significant positive effect on stock prices. determinant coefficient used while testing how much ability of independent variables in explaining the dependent variable. The results of data analysis showed Return On Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER) partially affect stock prices. oefisien determinant of t test concluded that the dependent variable can be explained by vriabel-independent variables of 31.4% and the remaining 68.6% influenced by other factors beyond the variables studied. Results of this study was successful because of the independent variables can explain the dependent variable of more than 50%.